Interaction of Alphabet Movement Activity on Attention and Memory of Early Childhood - Fitri, Ruqoyyah; Yatim Riyanto; Miftakhul Jannah (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Physical activity in early childhood is crucial for physical, cognitive, social, emotional development, as well as to train their motor skills. Physical motor learning contributes to the development of basic skills and the improvement of other aspects. One of the methods applied is the alphabet movement learning model, which has an important role in the growth of early childhood, especially in supporting attention and memory abilities, which are the foundation in the development process. This study aims to analyze the interaction of alphabet movement activity on the attention and memory of early childhood. This study used a quasi-experimental Nonrandomized Pretest-Posttest Control Group design involving 100 children who were divided into an experimental group (n = 50) and a control group (n = 50). The experimental group was given additional locomotor and non-locomotor movements that interpreted the alphabet, while the control group followed the regular curriculum. The results showed that the experimental group had higher attention and memory abilities, which were caused by the multisensory approach and coordinative movements that improved body movement control and optimized cognitive function.